Language and identity - Mantero, Miguel; Watzke, John L.; Miller, Paul Chamness (Readings in language studies., 2022)
Language and Identity is the third volume of the Readings in Language Studies series published by the International Society for Language Studies, Inc. Edited by Paul Chamness Miller, John L. Watzke, and Miguel Mantero, volume three sustains the society's mission to organize and disseminate the work of its contributing members through peer-reviewed publications. The book presents international perspectives on language and identity in several thematic sections: discourse, culture, identity in the professions, policy, pedagogy, and the learner. A resource for scholars and students, Language and Identity, represents the latest scholarship in new and emergent areas of inquiry.